2010
DOI: 10.1007/s10071-010-0362-5
|View full text |Cite
|
Sign up to set email alerts
|

Reputation-like inference in domestic dogs (Canis familiaris)

Abstract: Humans frequently interact with strangers absent prior direct experience with their behavior. Some conjecture that this may have favored evolution of a cognitive system within the hominoid clade or perhaps the primate order to assign reputations based on third-party exchanges. However, non-primate species' acquisition of skills from experienced individuals, attention to communicative cues, and propensity to infer social rules suggests reputation inference may be more widespread. We utilized dogs' sensitivity t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 25 publications
1
55
1
1
Order By: Relevance
“…In previous studies claiming dogs' sensitivity to thirdparty interactions (Kundey et al, 2011;Marshall-Pescini et al, 2011), dogs might have approached the person or place that was associated with food. In fact Nitzschner et al, (2012Nitzschner et al, ( , 2014 suggested that multiple cues might influence dogs' choices, such as where donors stood and several features of the beggar's behaviour.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In previous studies claiming dogs' sensitivity to thirdparty interactions (Kundey et al, 2011;Marshall-Pescini et al, 2011), dogs might have approached the person or place that was associated with food. In fact Nitzschner et al, (2012Nitzschner et al, ( , 2014 suggested that multiple cues might influence dogs' choices, such as where donors stood and several features of the beggar's behaviour.…”
Section: Discussionmentioning
confidence: 97%
“…This sensitivity has been tested in a few nonhuman species including chimpanzees, Pan troglodytes (Subiaul, Vonk, OkamotoBarth, & Barth, 2008), tufted capuchin monkeys, Cebus apella , common marmosets, Callithrix jacchus (Kawai, Yasue, Banno, & Ichinohe, 2014), domestic dogs, Canis familiaris (Freidin, Putrino, D'Orazio, & Bentosela, 2013;Kundey et al, 2011;Marshall-Pescini, Passalacqua, Ferrario, Valsecchi, & Prato-Previde, 2011;Nitzschner, Kaminski, Melis, & Tomasello, 2014;Nitzschner, Melis, Kaminski, & Tomasello, 2012), and Labroides dimidiatus cleaner fish (Bshary & Grutter, 2006). In most of these studies the participants watched third-party interactions, usually exchanges, involving food, which raises the possibility that participants simply preferred actors who were more likely to give them a better chance of getting food.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…This study may suggest that dogs evaluate characteristics of actors from third-party interactions, but a simple association between the generous donor and the reward cannot be ruled out. In Kundey et al (2011), dogs observed interactions between a recipient and two demonstrators, who both showed a treat to the recipient but then either gave it to her or not. Subsequently, when dogs were allowed to choose one of the demonstrators, they showed a strong preference for the giver.…”
Section: Introductionmentioning
confidence: 97%
“…Dogs might be able to make reputation-like inference by observing third-party interactions (Kundey et al, 2011;Marshall-Pescini et al, 2011; but see Nitzschner et al, 2012). And there is very clear evidence that they evaluate humans on the basis of direct experiences, i.e., searching for contact with a 'nice' experimenter-compared to an ignoring experimenter (Nitzschner et al, 2012).…”
Section: Monitoringmentioning
confidence: 98%